Teknologi Budidaya Jeruk di Lahan Gambut untuk Meningkatkan Produktivitas dan Pendapatan Petani di Kabupaten Tanjung Jabung Barat - Primilestari, Suci; Purnama, Hendri (Seminar Nasional Lahan Suboptimal, 2019)
Primilestari S, Purnama H. 2019. Citrus fruit cultivation technology in peatland to improve productivity and farmer’s income in tanjung Jabung Barat District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 79-89. Palembang: Unsri Press. Tanjung Jabung Barat District is a part of the development area of national citrus horticulture area located in Jambi Province. The area is a peatland which is suboptimal land, constrained by the nature of acid soils. Another obstacle is the low availability of quality and certified seeds, the level of pest and disease attacks is quite high due to the excessive use of pesticides, and nonoptimal plant maintenance. This paper aims to provide information on the implementation of technology and suggest improvements for the community and related stakeholders. This paper is a scientific review of location-specific technology innovations for citrus cultivation to applied on peatlands, including site-specific fertilization and calcification by the results of soil analysis, improved land sanitation and environmentally friendly pest and disease control. The implementation of location-specific technology on peatland in Tanjung Jabung Barat Regency is necessary to increase citrus productivity so that farmers' welfare can be achieved.Keywords: citrus, calcification, cultivation technology,  fertilization, peatlands